13N-ammonia PET/CT stress myocardial blood flow compared to fractional flow reserve in coronary artery disease. Issue 2 (February 2020) - Boer, Jouke J.; Kappelhof, Johan J.J.S.; van der Zant, Friso M.; Wondergem, Maurits; de Swart, Hans(J) B.R.M.; Knol, Remco J.J.
Abstract : Aim: In this retrospective study, fractional flow reserve was compared to stress myocardial blood flow derived by 13 N -ammonia ( 13 N -NH3 ) myocardial perfusion PET/CT. Methods: From a large cohort of patients referred for 13 N -NH3 PET/CT, patients who also had fractional flow reserve-measurements within 6 months of the PET study were selected. These fractional flow reserve measurements were compared to PET/CT derived stress myocardial blood flow of the corresponding coronary territory. Results were categorized as concordant or discordant. Patients with discordant results were subdivided into a group with reduced fractional flow reserve but normal stress myocardial blood flow (group A) or into a group with normal fractional flow reserve but reduced stress myocardial blood flow (group B). Results: From September 2013 through July 2016, 46 patients examined with 13 N -NH3 PET/CT also had fractional flow reserve-measurements within 6 months. A total of 66 measurements were used for comparison. Discordance was found in 32% of the measurements. Group B showed a significant reduction in stress myocardial blood flow of all coronary territories compared to group A ( P = 0.000). During follow-up (median 3.96 years), group B showed more visits to the emergency department and newly developed heart failure. Conclusion: Discordance with stress myocardial blood flow in the corresponding flow territory was found in 32% of the fractional flow reserve-measurements. Patients with reduced stress myocardial blood flow but normal fractional flow reserve showed significantly reduced stress myocardial blood flow in all coronaries and a trend towards more cardiac adverse events.